2010
DOI: 10.1063/1.3516483
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of the effect of La2O3 incorporation on the flatband voltage and Si band bending in the TiN/HfO2/SiO2/p-Si stack

Abstract: Recent studies have shown that La 2 O 3 films can be used to adjust the threshold voltage ͑V t ͒ of NMOS Hf-based high-k/metal gate devices to desirable values, and a dipole at the high-k / SiO 2 interface has been proposed to explain the V t shifts. In order to investigate the mechanism of the V t shift further, we have measured the flatband voltage ͑V fb ͒ and Si band bending of technologically relevant TiN/ HfO 2 / La 2 O 3 / SiO 2 / p-Si stacks where the thickness and position of the La 2 O 3 layer have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The detailed analysis for inconsideration of Si sub-oxidation has been given in our previous work [12]. The position of Si 2p core-level spectrum shown in Figure 2 is in agreement with the widely reported value for true position of Si 2p core-level, which is approximately in the range of 98-101 eV for Si 2p from Si substrate and 102-106 eV for Si 2p from SiO 2 [13][14][15][16][17][18]. The peak binding energies of Si 2p 3/2 core-level obtained by fitting the spectra in Figure 2 are summarized in Table 1.…”
Section: Details For C-v Measurementssupporting
confidence: 86%
“…The detailed analysis for inconsideration of Si sub-oxidation has been given in our previous work [12]. The position of Si 2p core-level spectrum shown in Figure 2 is in agreement with the widely reported value for true position of Si 2p core-level, which is approximately in the range of 98-101 eV for Si 2p from Si substrate and 102-106 eV for Si 2p from SiO 2 [13][14][15][16][17][18]. The peak binding energies of Si 2p 3/2 core-level obtained by fitting the spectra in Figure 2 are summarized in Table 1.…”
Section: Details For C-v Measurementssupporting
confidence: 86%
“…This is attributed to thicker silicon oxide interlayers formed between MgO and Si. It has been shown that an additional oxide layer in the oxide stack leads to a change in VBO [10]. The VBO change is due to the potential drop across the additional oxide layer, which should be added to the total band offset, makes the barrier higher.…”
Section: Discussionmentioning
confidence: 98%
“…[5][6][7][8] Alternatively, it was shown that thin dielectrics layers, so called capping layers, placed at the metal-dielectric interface, can be useful for controlling the EWF. 9,10 Typically, Al oxide is used for increasing the EWF 11,12 and La oxide [13][14][15][16] (and to some extent Gd oxide 17,18 ) for decreasing the EWF. It was shown that the position of the capping layers' atoms is important for their functionality, 19,20 and particularly it was shown with different configurations that the contact of Al oxide with SiO 2 is responsible for the EWF increase.…”
Section: Introductionmentioning
confidence: 99%